2021
DOI: 10.1186/s12870-021-03377-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy to uncover specific GO terms/phosphorylation pathways in phosphoproteomic data in Arabidopsis thaliana

Abstract: Background Proteins are the workforce of the cell and their phosphorylation status tailors specific responses efficiently. One of the main challenges of phosphoproteomic approaches is to deconvolute biological processes that specifically respond to an experimental query from a list of phosphoproteins. Comparison of the frequency distribution of GO (Gene Ontology) terms in a given phosphoproteome set with that observed in the genome reference set (GenRS) is the most widely used tool to infer bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Many of the phosphosites identified in this study have already been reported as early light-induced ones: CRY2 is phosphorylated by light in Yp 604 (p-value = 0.017) (Table 1) (Liu et al, 2017), while PHOT1 is phosphorylated in Sp 13 (p-value = 10 0.014), Sp 23 (p-valor = 0.008), Sp 382 (p-valor = 0.051) and Sp 409 (p-valor = 0.022) (Table 1) (Inoue et al, 2008;Sullivan et al, 2008;Deng et al, 2014). In a previous study we found that the GO (Gene Ontology) terms "regulation of mRNA splicing" and "cytoplasmic MTs compounds" were specifically enriched in the phosphoproteome of dark-grown Arabidopsis seedlings (Arico et al, 2021). None of the 40 unique phosphoproteins related to "regulation of mRNA splicing" identified in darkness (Arico et al, 2021) changes their phosphorylation status after 20 min of light.…”
Section: Maps Are Overrepresented In the Early Light-induced Phosphop...mentioning
confidence: 88%
See 2 more Smart Citations
“…Many of the phosphosites identified in this study have already been reported as early light-induced ones: CRY2 is phosphorylated by light in Yp 604 (p-value = 0.017) (Table 1) (Liu et al, 2017), while PHOT1 is phosphorylated in Sp 13 (p-value = 10 0.014), Sp 23 (p-valor = 0.008), Sp 382 (p-valor = 0.051) and Sp 409 (p-valor = 0.022) (Table 1) (Inoue et al, 2008;Sullivan et al, 2008;Deng et al, 2014). In a previous study we found that the GO (Gene Ontology) terms "regulation of mRNA splicing" and "cytoplasmic MTs compounds" were specifically enriched in the phosphoproteome of dark-grown Arabidopsis seedlings (Arico et al, 2021). None of the 40 unique phosphoproteins related to "regulation of mRNA splicing" identified in darkness (Arico et al, 2021) changes their phosphorylation status after 20 min of light.…”
Section: Maps Are Overrepresented In the Early Light-induced Phosphop...mentioning
confidence: 88%
“…In a previous study we found that the GO (Gene Ontology) terms "regulation of mRNA splicing" and "cytoplasmic MTs compounds" were specifically enriched in the phosphoproteome of dark-grown Arabidopsis seedlings (Arico et al, 2021). None of the 40 unique phosphoproteins related to "regulation of mRNA splicing" identified in darkness (Arico et al, 2021) changes their phosphorylation status after 20 min of light.…”
Section: Maps Are Overrepresented In the Early Light-induced Phosphop...mentioning
confidence: 92%
See 1 more Smart Citation
“…Total protein extraction, trypsin digestion of proteins, phosphopeptides enrichment and LC–MS/MS (Figure S1) is fully described in Arico et al. (2021). Three biological replicates per condition were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study we found that the Gene Ontology terms "regulation of mRNA splicing" and "cytoplasmic microtubule compounds" were specifically enriched in the phosphoproteome of dark-grown Arabidopsis seedlings (Arico et al, 2021). None of the 40 unique phosphoproteins related to "regulation of mRNA splicing" identified in darkness changes their phosphorylation status after 20 min of light (Arico et al, 2021). The bioinformatic tool MAPanalyzer allows the analysis of known or predicted ones (Zhou et al, 2015).…”
Section: Maps Are Overrepresented In the Early Light-induced Phosphop...mentioning
confidence: 99%